(untitled) (Fiep Bulletin - online, 2014)
The African matrices provide an indispensable contribution in the process of human development, it will evoke coping with diversity, with different and worthy human, respecting it in its otherness, valuing and recognizing their rights, their ways of being, acting and being in the world. Educating for human development is synonymous with education for the real exercise of citizenship, which ultimately equates to educate the recognition, respect and appreciation of human dignity. The values ?? of an ancient culture have been relegated to the educational process, and therefore have rested quietly a systematic practice of denial of the elements of africanidades mode of teaching and learning, both from the point of view of the methods, as the contents. Promote humanity in the context of adversity is to dream and pursue the utopia of a fairer, more humane and dignified for all segments of society.